Atmospheric benzene observations from oil and gas production in the Denver‐Julesburg Basin in July and August 2014. Issue 18 (20th September 2016) - Halliday, Hannah S.; Thompson, Anne M.; Wisthaler, Armin; Blake, Donald R.; Hornbrook, Rebecca S.; Mikoviny, Tomas; Müller, Markus; Eichler, Philipp; Apel, Eric C.; Hills, Alan J.
Abstract: High time resolution measurements of volatile organic compounds (VOCs) were collected using a proton‐transfer‐reaction quadrupole mass spectrometry (PTR‐QMS) instrument at the Platteville Atmospheric Observatory (PAO) in Colorado to investigate how oil and natural gas (O&NG) development impacts air quality within the Wattenburg Gas Field (WGF) in the Denver‐Julesburg Basin. The measurements were carried out in July and August 2014 as part of NASA's "Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality" (DISCOVER‐AQ) field campaign. The PTR‐QMS data were supported by pressurized whole air canister samples and airborne vertical and horizontal surveys of VOCs. Unexpectedly high benzene mixing ratios were observed at PAO at ground level (mean benzene = 0.53 ppbv, maximum benzene = 29.3 ppbv), primarily at night (mean nighttime benzene = 0.73 ppbv). These high benzene levels were associated with southwesterly winds. The airborne measurements indicate that benzene originated from within the WGF, and typical source signatures detected in the canister samples implicate emissions from O&NG activities rather than urban vehicular emissions as primary benzene source. This conclusion is backed by a regional toluene‐to‐benzene ratio analysis which associated southerly flow with vehicular emissions from the Denver area. Weak benzene‐to‐CO correlations confirmed that traffic emissions were not responsible for the observed high benzene levels. Previous measurements at the Boulder Atmospheric Observatory (BAO) and our data obtained at PAO allow us to locate the source of benzene enhancements between the two atmospheric observatories. Fugitive emissions of benzene from O&NG operations in the Platteville area are discussed as the most likely causes of enhanced benzene levels at PAO. Key Points: Unexpectedly high benzene mixing ratios were observed in Colorado's Wattenburg Gas Field in July and August 2014 Oil and natural gas extraction activities are implicated as the primary source for the high benzene observations Gas field measurements of VOCs put a spatial constraint on the location of the gas field benzene source